Airplane Landing by the Curvilinear Glide Paths in Limits of the Border Trajectories Modelling Method - Voloshenyuk, D.A. (Управляющие системы и машины, 2017)
A new airplane landing method, that would correspond to the modern civil aviation requirements and assured ecological and economical level enhancement is considered. We present the generation method (calculation and construction) development and modeling of the virtual curvilinear airplane landing descending glide path in the limits of the border trajectories with sustaining of own individual, optimal vertical landing descending profile from flight level to the runway threshold. Рассмотрен новый метод посадки самолетов, который будет соответствовать современным требованиям гражданской авиации и обеспечит повышение уровня экологичности и экономичности полетов. Изучено моделирование метода генерации виртуальной криволинейной глиссады посадочного снижения самолета в рамках предельных траекторий с поддержанием индивидуального, оптимального, вертикального профиля снижения с эшелона полета до начала взлетно-посадочной полосы. Розглянуто новий метод посадки літаків, який відповідатиме сучасним вимогам цивільної авіації та забезпечить підвищення рівня екологічності та економічності польотів. Досліджено моделювання роботи методу генерації віртуальної криволінійної глісади посадкового зниження літака в межах граничних траєкторій з підтриманням індивідуального, оптимального, вертикального профілю зниження з ешелону польоту до початку злітно-посадкової смуги.